The Health Sector in Eritrea - World Bank (Washington, DC, 2013)
This study serves as the preliminary basis for further rounds of discussions and analyses among stakeholders to arrive at a strategic vision for the Eritrea health sector. It incorporates comments received from the Ministry of Health's central agencies, Zoba (regional) health teams, external partners working in Eritrea, and the World Bank Eritrea Country Team. In March 2001, the Ministry of Health of the Government of Eritrea launched a process to prepare a long-term health sector policy and strategic plan (HSPSP), with a focus on assuring equitable, quality, and sustainable health care. The Ministry outlined an open, participatory, three-step process for developing the HSPSP, with active participation from all partners in the health sector.